A European survey on awareness of post-surgical adhesions among gynaecological surgeons - Wallwiener, Markus; Koninckx, Philippe Robert; Hackethal, Andreas; Brölmann, Hans; Lundorff, Per; Mara, Michal; Wattiez, Arnaud; Wilde, Rudy Leon De (Gynecological surgery, 2014)
The present survey was conducted among gynaecological surgeons from several European countries to assess the actual knowledge and practice related to post-surgical adhesions and measures for reduction. From September 1, 2012 to February 6, 2013, gynaecological surgeons were invited to answer an 18-item online questionnaire accessible through the ESGE website. This questionnaire contained eight questions on care settings and surgical practice and ten questions on adhesion formation and adhesion reduction. Four hundred fourteen surgeons participated; 70.8 % agreed that adhesions are a source of major morbidity. About half of them declared that adhesions represented an important part of their daily medical and surgical work. About two thirds informed their patients about the risk of adhesion. Most cited causes of adhesions were abdominal infections and extensive tissue trauma, and endometriosis and myomectomy surgery. Fewer surgeons expected adhesion formation after laparoscopy (18.9 %) than after laparotomy (40.8 %); 60 % knew the surgical techniques recommended to reduce adhesions; only 44.3 % used adhesion-reduction agents on a regular basis. This survey gives a broad picture of adhesion awareness amongst European gynaecological surgeons, mainly from Germany and the UK. The participants had a good knowledge of factors causing adhesions. Knowledge of surgical techniques recommended and use of anti-adhesion agents developed to reduce adhesions need to be improved.